Techno-economic survey and design of a pilot test rig for a trilateral flash cycle system in a steel production plant. (September 2017) - McGinty, Rebecca; Bianchi, Giuseppe; Zaher, Obadah; Woolass, Steven; Oliver, David; Williams, Christopher; Miller, Jeremy
Abstract: In recent years the interest in recovering rejected low-grade heat within industry has intensified. Around 30% of global primary energy consumption is attributed to the industrial sector and a significant portion of this is rejected as heat. The majority of this wasted energy is available at temperatures below 100°C and as such conventional waste heat to power conversion systems cannot economically recover the energy, producing simple pay backs that are unacceptable to industry. The Trilateral Flash Cycle (TFC) is however a promising technology with the ability to harness the rejected heat found in these low grade waste streams. The current research work presents a techno-economic assessment of the installation potential for a low grade heat to power conversion system using a TFC system. In particular, thermodynamic modelling is utilised to estimate the expected energy recovery and, in turn, the potential savings achievable through the TFC solution. The survey investigated three diverse and challenging heat sources at steel production plants. Annual energy recovery from the chosen heat source is expected to be 782 MWh. Prior to the upscaling of the system to the 2MW waste thermal power, a pilot test rig was designed and built. Preliminary tests showed a net electrical power output up to 6.2 kW and an overall efficiency of 4.3%.